2018
DOI: 10.1155/2018/8968573
|View full text |Cite
|
Sign up to set email alerts
|

Study on Association of Pentraxin 3 and Diabetic Nephropathy in a Rat Model

Abstract: Diabetic nephropathy (DN) is a serious microvascular complication of diabetes. Compared with other therapies for diabetic patients, islet transplantation can effectively prevent and reverse diabetes-induced microvascular disease, such as diabetic retinopathy and nephropathy. PTX3 is the only long pentraxin that can be detected in renal tissue. In this study, we investigated the expression of PTX3 when early DN was reversed after islet transplantation. Methods. Diabetes was induced in rats by injecting streptoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…PTX 3 prevents injury by reducing ROS, inhibiting calpain/caspase-3, stabilizing mitochondria and IL-6/Stat3 pathway suppression (47,48). Conversely, it might promote injury by inducing adhesion molecules/chemokines, regulating leukocyte recruitment, and overactivating complement in kidney injury models (49,50). Elevated PTX 3 levels are associated with higher CKD patient mortality, increased CKD and CVD risk (19,20,51).…”
Section: Discussionmentioning
confidence: 99%
“…PTX 3 prevents injury by reducing ROS, inhibiting calpain/caspase-3, stabilizing mitochondria and IL-6/Stat3 pathway suppression (47,48). Conversely, it might promote injury by inducing adhesion molecules/chemokines, regulating leukocyte recruitment, and overactivating complement in kidney injury models (49,50). Elevated PTX 3 levels are associated with higher CKD patient mortality, increased CKD and CVD risk (19,20,51).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated PTX3 role in Diabetic Nephropathy (DN): in renal tissue of diabetic patients, Chen et al showed that PTX3 levels are closely related to renal injury thus suggesting its ability to quantify the extent of renal injury as early indicator of renal tubular injury but also injury progression on time [61].…”
Section: Ptx3 and Glomerulonephritismentioning
confidence: 99%
“…PTX-3, a member of the conservative protein superfamily, is a multimeric inflammatory mediator and a better inflammatory marker than hs-CRP (Uzun et al, 2016). PTX-3 is the only long pentraxin protein detectable in kidney tissue and is closely associated with kidney damage in DN (Chen et al, 2018). There is a very close relationship between SNPs in PTX-3…”
Section: Ptx-3mentioning
confidence: 99%